2016
DOI: 10.1161/strokeaha.116.012923
|View full text |Cite|
|
Sign up to set email alerts
|

Carotid Atherosclerotic Plaque Characteristics on Magnetic Resonance Imaging Relate With History of Stroke and Coronary Heart Disease

Abstract: Background and Purpose-Because atherosclerosis is a systemic disease, presence and composition on 1 location may relate to ischemic events in distant locations. We examined whether carotid atherosclerotic wall thickness, stenosis, and plaque composition are related to history of ischemic stroke and coronary heart disease (CHD). Methods-From the population-based Rotterdam Study, 1731 asymptomatic participants (mean age, 72.4±9.1 years; 55% males) underwent magnetic resonance imaging of both carotid arteries. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 37 publications
(11 reference statements)
0
30
0
2
Order By: Relevance
“…Our results indicate that the hypertriglyceridemic waist is significantly more prevalent among those with subclinical carotid atherosclerosis in comparison to those without. Furthermore, carotid maximum wall thickness, a marker widely used to inform about the presence of atherosclerosis, was positively associated with the hypertriglyceridemic waist. In comparison to the maximum wall thickness, carotid artery wall volume is more suitable to better inform about the true burden of atherosclerosis, because it measures the whole circumference of the artery over its entire length of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the hypertriglyceridemic waist is significantly more prevalent among those with subclinical carotid atherosclerosis in comparison to those without. Furthermore, carotid maximum wall thickness, a marker widely used to inform about the presence of atherosclerosis, was positively associated with the hypertriglyceridemic waist. In comparison to the maximum wall thickness, carotid artery wall volume is more suitable to better inform about the true burden of atherosclerosis, because it measures the whole circumference of the artery over its entire length of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, CTRP9 could play multiple positive roles in vascular lesion as a key in the pathogenesis of cardiovascular disease (Figure ). CAD and ischemic stroke are both the major subtypes of atherosclerotic vascular diseases which share a large of similar pathogenesis from risk factors to vascular lesions followed with target organ damage (Selwaness et al, ), as well as a serial of common treatment strategies including antithrombotic therapy, blood lipids adjustment, blood pressure control, and blood glucose regulation (Powers et al, ; Valgimigli et al, ). Due to the different target organs, atherosclerotic lesions result in distinct clinical manifestations in CAD and ischemic stroke, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Yang-Ha Hwang, et al reported that in situ thrombo-occlusion with underlying intracranial atherosclerotic disease may contribute to residual stenosis which leads to instant or delayed reocclusion in intracranial large artery atherosclerosis disease [24]. It may be that residual stenosis exists in patients with acute ischemic stroke due to large artery atherosclerosis who were ever subjected to ischemic stroke [25]. One of causes led to rescue therapy in large artery atherosclerosis is repeatedly reocclusion during the procedure, and residual stenosis in patients with prestroke incidence may be the key to the repeatedly reocclusion.…”
Section: Discussionmentioning
confidence: 99%